Modeling of Virus Survival Time in Respiratory Droplets on Surfaces: A New Rational Approach for Antivirus Strategies - Di Novo, N. G.; Carotenuto, A. R.; Mensitieri, G.; Fraldi, M.; Pugno, N. M. (Frontiers in Materials, 2021)
The modelling of the viability decay of viruses in sessile droplets is addressed considering a droplets sitting on a smooth surface characterized by a specific contact angle. To investigate, at prescribed temperature, how surface energy of the material and ambient humidity cooperate to determine the virus viability we propose a model which involves the minimum number of thermodynamically relevant parameters. In particular, by considering a saline water droplet (one salt) as the simplest approximation of real solutions (medium and natural/artificial saliva), the evaporation is described by a first-order time-dependent nonlinear differential equation properly rearranged to obtain the contact angle evolution as the sole unknown function. The analyses were performed for several contact angles and two typical droplet sizes of interest in real situations, by assuming constant ambient temperature and relative humidity in the range 0-100%. The results of the simulations, given in terms of time evolution of salt concentration, vapour pressure and droplet volume, elucidate some previously not yet well understood dynamics, demonstrating how three main regimes –directly implicated in non-trivial trends of virus viability and to date only highlighted experimentally –can be recognized as function of the relative humidity. By recalling the concept of cumulative dose of salts (CD), to account for the effect of the exposition of viruses to salt concentration on virus viability, we show how the proposed approach could suggest a chart of a virus fate by predicting its survival time at a given temperature as a function of the relative humidity and contact angle. We found a good agreement with experimental data for various enveloped viruses by predicting in particular for the Phi6 virus, a surrogate of coronaviruses, the characteristic U-shaped dependence of viability on relative humidity. Given the generality of the model and once experimental data are available that link the vulnerability of a certain virus, such as SARS-CoV 2, to the concentrations of salts or other substances in terms of CD, it is felt that this approach could be employed for anti-virus strategies and for protocols for the prediction / reduction of human health risks associated with SARS-CoV-2 and other viruses.